Epigenetic correlates of plant phenotypic plasticity: DNA methylation differs between prickly and nonprickly leaves in heterophyllous Ilex aquifolium (Aquifoliaceae) trees. (13th December 2012) - Herrera, Carlos M.; Bazaga, Pilar
<x xml:space="preserve">Abstract</x> Phenotypic plasticity is central to the persistence of populations and a key element in the evolution of species and ecological interactions, but its mechanistic basis is poorly understood. This article examines the hypothesis that epigenetic variation caused by changes in DNA methylation are related to phenotypic plasticity in a heterophyllous tree producing two contrasting leaf types. The relationship between mammalian browsing and the production of prickly leaves was studied in a population of Ilex aquifolium (Aquifoliaceae). DNA methylation profiles of contiguous prickly and nonprickly leaves on heterophyllous branchlets were compared using a methylation‐sensitive amplified polymorphism (MSAP) method. Browsing and the production of prickly leaves were correlated across trees. Within heterophyllous branchlets, pairs of contiguous prickly and nonprickly leaves differed in genome‐wide DNA methylation. The mean per‐marker probability of methylation declined significantly from nonprickly to prickly leaves. Methylation differences between leaf types did not occur randomly across the genome, but affected predominantly certain specific markers. The results of this study, although correlative in nature, support the emerging three‐way link between herbivory, phenotypic plasticity and epigenetic changes in plants, and also contribute to the crystallization of the consensus that epigenetic variation can complement genetic variation as a source of phenotypic variation in natural plant populations. © 2012 The Linnean Society of London